Pengaruh Beban Kerja, Human Relationship, dan Organizational Citizenship Behavior (OCB) Terhadap Kinerja Pegawai (Pada Pegawai Negeri Sipil BKPSDM Kabupaten Tulungagung) - Annisa Sari; Abdul Kodir Djaelani; Eka Farida (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study was conducted to examine workload, human relationship, and organizational citizenship behavior (OCB) on employee performance. This study uses explanatory research by using primary and secondary data as a data source. Sampling techniques and populations using non probability sampling techniques with saturated sampling. The samples used are all employees of BKPSDM Tulungagung Regency as many as 52 ASN status. The analyses used are instrument tests, classic assumption tests, multiple linear regressions, hypothesis tests, and adjusted R2 coefficients.The results showed, workload, human relationship, and organizational citizenship behavior (OCB) affect the performance of employees BKPSDM Tulungagung, workload has a positive and significant effect on the performance of employees of BKPSDM Tulungagung Regency, human relationship has a positive and significant effect on the performance of employees BKPSDM Tulungagung, organizational citizenship behavior (OCB) does not have a significant influence on the performance of employees BKPSDM Tulungagung. Keywords: Workload, Human Relationship, Organizational Citizenship Behavior (OCB), Employee Performance